A Mobile Based Technology to Improve Male Involvement in Antenatal Care. - Gloria, Muhoza B.; Mukasa, Ssemaluulu Paul; Mabirizi, Vicent (Kabale University, 2023)
The World Health Organization Technical Working Group on maternal health unit recommended a minimum level of care to be four visits throughout the pregnancy for pregnant mothers [1]. The first visit which is expected to screen and treat anaemia, syphilis, screen for risk factors and medical conditions that can be best dealt with in early pregnancy and initiate prophylaxis if required (e.g., for anaemia and malaria) is recommended to be made before the end of the fourth month of pregnancy. The second, third and fourth visits are scheduled at 24–28, 32 and 36 weeks, respectively. Male involvement in Antenatal health care has been described as a process of social and behavioral change that is needed for men to play more responsible roles in maternal health care with the aim of ensuring women and children’s wellbeing. A study by Okoth [1] reported that, in Uganda male involvement in antenatal care stands at only 6% and this has been attributed to social, economic and cultural related factors. The situation worsens with the lack of effective coordinated platform for males sharing their experience in taking part in ANC and this has affected the process of antenatal care service delivery. Objective. To assess the role of mobile technology to improving male involvement in antenatal care by developing a mobile based technology which sends SMS reminders to male partners encouraging them to escort their pregnant wives for antenatal care services. Research questions. What are the challenges towards the limited antenatal care seeking behaviours among pregnant mothers? What are the causes of limited male involvement in antenatal care? What roles do ICTs play in enhancing Antenatal Care seeking behaviours among pregnant mothers and in increasing the male involvement in Antenatal Care? Method. We purposively selected pregnant mothers who phones, had been receiving antenatal care services from Kabale general hospital and reported staying with her male partner. The recruited participants were interviewed together with their male partners. STATA 13 software was used to define participants’ demographic while qualitative data were analysed using content analysis to come up with classes describing participants’ perceptions. Results. Participants reported that reminding them of their next antenatal visit via SMS reminder plays a significant role towards their antenatal care seeking behaviour. Conclusion. Mobile health could be a potential approach to improving male involvement in antenatal care through sending timely SMS reminders to both the expectant mother and her male partner remaining them of their next antenatal visit. Keywords: Antenatal Care, Male Involvement, Mobile Health Care, Digital Health.